2009
DOI: 10.1152/ajpregu.00045.2009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β mediates increased activation of PI3K/Akt signaling and improved myocardial function in female hearts following acute ischemia

Abstract: Females have a lower incidence of heart failure and improved survival after myocardial ischemia-reperfusion (I/R) compared with males. Although estrogen-suppressed cardiomyocyte apoptosis may be mediated through the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway, it is unclear whether this action is mediated via estrogen receptor beta (ERbeta). Therefore, we hypothesized that ERbeta mediates estrogen-induced cardioprotection through PI3K/Akt and antiapoptotic signaling in females but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 26 publications
4
82
2
1
Order By: Relevance
“…Since treatment of the ovariectomized rat with estrogen resulted in an increase in the basal level of caspase 3 protein, it can be suggested that caspase 3 protein level is dependent on functioning ovaries. In fact, Wang et al [43] have recently reported that myocardial protection following ischemia-reperfusion by upregulating the PI3K/ Akt pathway whereas decreased caspase 3 and 9 and increased Bcl-2 in female hearts is mediated through estrogen receptor, ERb. In summary, this is the first study to clearly identify gender differences in cardiomyocyte apoptosis and pro-and anti apoptotic factors in hearts subjected to volume overload.…”
Section: Discussionmentioning
confidence: 99%
“…Since treatment of the ovariectomized rat with estrogen resulted in an increase in the basal level of caspase 3 protein, it can be suggested that caspase 3 protein level is dependent on functioning ovaries. In fact, Wang et al [43] have recently reported that myocardial protection following ischemia-reperfusion by upregulating the PI3K/ Akt pathway whereas decreased caspase 3 and 9 and increased Bcl-2 in female hearts is mediated through estrogen receptor, ERb. In summary, this is the first study to clearly identify gender differences in cardiomyocyte apoptosis and pro-and anti apoptotic factors in hearts subjected to volume overload.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of Bcl-2 secondary to the activation of NF-jB might be mediated by the overexpression of p53 (Aoki et al 2001). A previous study reported the significant increase in the expression of p53 in microgravity-exposed cells (Wang et al 2009b). Therefore, we deduced that the activation of NF-jB probably induced HPMEC apoptosis through the suppression of Bcl-2 under simulated microgravity conditions.…”
Section: Discussionmentioning
confidence: 89%
“…The PI3K/Akt pathway is involved in the acute nongenomic actions of 17βE2 in various cells types [32], as well as in many responses elicited by this hormone at the level of cardiac myocytes [46]. Its implication in 17βE2 effects has been related especially to heart protection against ischemia [47]. Upregulation of PI3K/Akt by 17βE2 results in eNOS activation via a transcription-independent mechanism [48,49] which is mainly associated with ERα activation [32].…”
Section: Discussionmentioning
confidence: 99%